FEATURES OF ANTI-UKRAINIAN INFORMATION (CYBER) INFLUENCE ON UKRAINE - Levchenko, Oleksandr; Okhrimchuk, Volodymyr (Ukrainian Information Security Research Journal, 2023)
Since the day of independence of Ukraine, its information space and cyberspace, after the development and implementation of information technologies in all spheres of society, are constantly under powerful foreign informational and cybernetic influences. The hybrid war launched by Russia in 2014 forced Ukraine to reconsider its approaches to ensuring information and cyber security. And with the beginning of a large-scale invasion, this issue became especially urgent. To carry out anti-Ukrainian information (cyber) influence, the Russian leadership used significant human, material and financial resources, thanks to which it was possible to effectively "brainwash" not only the majority of its citizens, but also a part of our compatriots. Therefore, unfortunately, this led to the support of a part of the Ukrainian citizens of the Kremlin's aggressive policy against Ukraine. The article analyzed the main information operations of Russia against Ukraine, as well as the implementation of cyber-attacks on its critical information infrastructure. As a result of the analysis, the features of anti-Ukrainian information (cyber) influence on Ukraine were established. Knowledge of the features of the enemy's destructive actions in the information and cyberspace will make it possible to create effective methods and means of countering them in the future.